Pangan yang difortifikasi zat gizi mikro pada ibu hamil meningkatkan perkembangan motorik bayi - Bernatal Saragih; Hidayat Syarief; Hadi Riyadi; Amini Nasoetion (Jurnal Gizi Klinik Indonesia, 2012)
Background: Many factors infl uence the growth and development of an infant but nutrition was undeniably one of the most important factors. One way to improve the nutritional status of infants was by providing supplementary foods fortifi ed with multiple micronutrients to mothers during pregnancy. Nutritional interventions during pregnancy provided better nutrient reserves for mothers and fetus.Objective: To analyze the impact of multi micronutrient-fortifi ed supplementary foods provision in pregnant mothers on motor development and anemia status of infants in three sub-districts of Bogor District namely: Leuwiliang, Leuwisadeng and Ciampea.Method: A total of 120 infants were followed up in a prospective cohort study. The subjects were divided into three groups, i.e: 40 infants in fortifi ed group (pregnant mothers received supplementary foods (vermicelli, milk and biscuit) fortifi ed with multi-nutrients i.e. iron, iodine, zinc, folic acid, vitamin C and vitamin A), 40 infants in non-fortifi ed groups (pregnant mothers received non fortifi ed foods) and 40 infants in the control groups (pregnant mothers did not receive any supplementary foods). Motor development was measured by methods developed by the Ministry of Health, Republic of Indonesia. Hb was measured by Cyanmethemoglobin method. Ancova and linear logistic regression were used to analyze the data.Results: Provision of multi micronutrient-fortifi ed supplementary foods in pregnant mothers substantially improves infant’s motor development (77% better than other groups). In addition, supplementation of multi micronutrient-fortifi ed foods in pregnant mothers reduced the rate of hemoglobin and hematocrit decline in infants up to the age of 6 months. There were no infants aged 6 months with Hb < 90 g / L in the fortifi ed group, while in the non-fortifi ed group and control group the prevalence of anemia was 8.3% and 11.11%, respectively.Conclusion: Provision of multi micronutrient-fortifi ed supplementary foods in pregnant mothers improved infant’s motor development.